Reformations and their impact on the culture of memoria - Bueren, Truus van 1946-; Cockerham, Paul; Horch, Caroline 1959-; Meuwese, Martine 1966-; Schilp, Thomas 1953-2019; Oexle, Otto Gerhard 1939-2016 (Memoria and remembrance practices, 2016)
"This volume presents cultural studies approaches to different modes of memoria (the original medieval way of commemoration), taking into account specific confessional contexts. It mainly focuses on the consequences of political, religious and social reforms in the period from 1200 to 1800. Scholars from multiple subject areas in the field of cultural studies evaluate if, and to what extent, reform processes and political or social change have influenced different practices of memoria. Since customs of commemoration of the dead (and the living) serve as a means of self-reassurance for a society, they allow significant insights into what the respective societies were grounded upon. This volume delivers the first discipline-specific and methodologically diverse approach to the consequences of different reforms on memoria. In this way this overview creates a "history of memoria" throughout the centuries."--Back cover